Pelatihan Pengolahan Air yang Berkelanjutan di Desa Pasiang, Polewali Mandar - Prameswara, Gyan; Setyorini, Dwi; Dahlan, Masbin; Assagaf, Iman Pradana A.; Raihan, Ahmad Zaki (Journal of Community Services in Sustainability, 2024)
The increasing demand for sustainable water treatment in regions with constrained access to clean water underscores the necessity for targeted interventions. This community service initiative (PKM) focused on establishing a sustainable water treatment training program in Pasiang Village, Polewali Mandar, with an emphasis on biofiltration technology. Utilizing a SWOT analysis and a pre- and post-program evaluation framework, the study assessed both the challenges and opportunities related to implementing a localized water treatment system. Findings highlighted the community’s reliance on groundwater sources and limited familiarity with surface water treatment technologies as primary obstacles. The training program encompassed both informational sessions on biofiltration technology and hands-on practice in operating the treatment system. Evaluations revealed notable advancements in participants' competencies, including a 50% improvement in practical skills, a 47% increase in technology utilization, and a 40% gain in foundational knowledge. Participant satisfaction ranged from 85% to 100% across program aspects, with particularly high ratings in program benefits and alignment with community needs. The adoption of biofiltration technology has demonstrated its viability as a sustainable water treatment solution in rural contexts, supported by substantial community engagement and comprehension of the technology. This PKM program thus offers a replicable model for developing sustainable water treatment training frameworks adaptable to similar communities.